Seedcoat chemist scarification to optimize the emergency and growth of Trifoliata rootstock - de Oliveira, Roberto Pedroso; Scivittaro, Walkyria Bueno; Radmann, Elizete Beatriz (Pesquisa Agropecuaria Brasileira, 2006)
The aim of this work was to evaluate the emergency and growth of the Trifoliata [Poncirus trifoliata (L.) Raf.] citrus rootstock, derived from chemically scarified seeds. The sowing was carried through in plastic dibble tubes, containing commercial substrate, in a greenhouse. The treatments consisted of chemical reference treatment of the seeds TQR (45-minute immersion in solution composed of 0.5 L NaClO 12%, 3 mL HCl and 20 g NaOH diluted in 2 L of water); half, double and four times TQR concentration; half and double immersion time of TQR; omission of NaClO; omission of HCl; omission of NaOH; control treatments comprising seeds with tegument and without tegument. The experiment was a randomized complete block design, with four replications and experimental units composed of 42 dibble tubes comprising one seed each. The emergence of Trifoliata seedlings occurred during the 6th to 45th day after sowing. Final percentage of emergence varies from 92.4 to 99.7%. Sixty five days after sowing, seeds submitted to the double concentration of TQR result in rootstocks with higher total dry matter (0.52 g per plant), and good height (15.2 cm) and shoot diameter (2.41 mm).